Low-exhaustion peripheral circulating γδ T cells serve as a biomarker for predicting the clinical benefit rate of non-small cell lung cancer (NSCLC) patients to chemotherapy or targeted therapy: a single-center retrospective study - Dongdong Zhang; Guichao Liu; Jinhui Ye; Ke Li; Guojun Zhang; Qiang Quan; Xinhai Zhu; Peng Li (BMC Cancer)
Abstract Background Multiple studies have demonstrated that the abundance and functionality of γδ T cells are favorable prognostic indicators for prolonged survival in cancer patients. However, the association between the immunophenotype of circulating γδ T cells and the therapeutic response in NSCLC patients undergoing chemotherapy or targeted therapy remains unclear. Methods Patients with EGFR wild-type (EGFR-WT) or mutant (EGFR-Mut) non-small cell lung cancer (NSCLC), diagnosed between January 2020 and January 2024, were included in this study. Clinicopathological characteristics, treatment regimens, and follow-up data were retrospectively collected. Peripheral blood samples from 52 NSCLC patients were analyzed for the immunophenotypes of αβ T cells and γδ T cells using full-spectrum flow cytometry. Results No significant differences were observed in the proportions of αβ T cells or γδ T cells, nor in the expression of immune exhaustion markers, between epidermal growth factor receptor wild-type and mutant NSCLC patients. Notably, NSCLC patients with a high clinical benefit rate (responder, R) exhibited a higher proportion of circulating Vδ2 T cells compared to non-responders (NR), in both EGFR-Mut (NR vs. R, P = 0.0437) and EGFR-WT groups (NR vs. R, P = 0.0180). Additionally, the expression of the immune exhaustion marker PD-1 on Vδ2 T cells was significantly lower in the responder group (NR vs. R, EGFR-Mut, P = 0.0050; EGFR-WT, P = 0.0180). Moreover, responder patients exhibited elevated levels of TNF-α compared to non-responders, irrespective of EGFR mutation status (NR vs. R, EGFR-Mut, P = 0.0055; EGFR-WT, P = 0.0007). Conclusions These findings collectively suggest that circulating Vδ2 T cells with low levels of immune exhaustion are critical contributors to the effectiveness of chemotherapy and targeted therapies in NSCLC. Targeting Vδ2 T cells may represent a promising strategy for enhancing therapeutic clinical benefit rates in NSCLC patients.